Reproductive Performance of Ongole Grade, Simmental, and Limousin Cattle Given Superovulation Treatment - Pangestu, Muhamad Syahid Panji; Darodjah, Siti; Hilmia, Nena; Imron, Muhamad (Faculty of Agriculture, 2024)
Reproductive technologies have the potential to enhance livestock productivity, with superovulation being one such method aimed at increasing the number of ovulated oocytes per estrous cycle through hormonal stimulation. This study aimed to evaluate the reproductive performance of three cattle breedsOngole Grade (OG) (n=20), Simmental (n=18), and Limousin (n=20)subjected to superovulation treatment. The cattle, aged 2.5 to 4 years with a body condition score of 3.5 to 4, were intensively managed. Superovulation was induced using CIDR (Controlled Internal Drug Release) for synchronization, followed by follicle-stimulating hormone (FSH) administration. Reproductive performance data, including age at first estrus, number of corpora lutea (CL), and embryo production, were collected over three estrous cycles. A quasi-experimental design was employed with breed as the primary treatment factor, and data were analyzed using analysis of variance (ANOVA). The results indicated that breed had a significant effect (P0.05) on the age of first estrus, with OG cattle reaching first estrus at 621.393.3 days, Simmental at 522.475.5 days, and Limousin at 570.488.1 days. However, no significant differences (P0.05) were observed among the breeds in terms of the number of CL, collected embryos, or transferable embryos across the superovulation cycles.